PERAN EWOM DALAM MEMEDIASI KUALITAS PRODUK DAN PERCEIVED VALUE TERHADAP KEPUTUSAN PEMBELIAN - Lucky, Ratna; Pramadanti, Rindika (Jurnal Bisnis Dan Kajian Strategi Manajemen, 2024)
This research aims to determine the influence of product quality and perceived value on electronic word of mouth through purchasing decisions as an intermediary variable. The research was conducted by 208 respondents at Fore Coffee, South Jakarta who had previously purchased products. The number of respondents was determined using the purposive sampling method, namely a sample selection technique with certain considerations. Data was obtained by distributing questionnaires which were analyzed using path analysis techniques and then processed using SEM PLS version 3.2.9. The test results state that the variables that positively influence electronic word of mouth include product quality and perceived value. Some variables can have a direct positive influence on purchasing decisions including product quality and perceived value. Meanwhile, those that have a direct negative influence on purchasing decisions include electronic word of mouth, and also variables that can influence indirectly through electronic word of mouth mediation and purchasing decisions are product quality and perceived value.Keywords: Product Quality, Perceived Value, Purchase decision, electronic word-of-mouth